Gender, migratory path and minority status. Sexual and preventive trajectories of sub-Saharan African migrants living in France - (:unkn) unknown (My University, 2012)
Migrants from sub-Saharan Africa bear a disproportionate burden of HIV/aids infections in France with a growing proportion acquiring HIV after migration. Mobilizing a sociological approach of sexuality, we focus on sexual trajectories and sexual networks in order to investigate the structural processes that organize the sexual and preventive practices of these migrants. We analyse a French survey carried out on 1,874 individuals born in sub-Saharan Africa, aged 18-49 and living in Paris and its surroundings. Our results uncover the effects of sexual socialization and social context of the first intercourse on sexual debuts and on later sexual and preventive biographies, differentiated for women and men. We also examine how migratory trajectories and experiences of racism and discrimination organize their sexual and preventive practices within specific sexual networks. Our research provides evidence of the existence of African sexual networks over, and beyond, national origin, especially for women. This intra-African segregation of sexual networks is influenced by the living conditions of the migrants and sheds light on the epidemic spread within these populations in the French context.
Keywords: African Research